Trajectories of mental health in children and adolescents during the COVID-19 pandemic: findings from the longitudinal COPSY study - Anne Kaman; Janine Devine; Markus Antonius Wirtz; Michael Erhart; Maren Boecker; Ann-Kathrin Napp; Franziska Reiss; Fionna Zoellner; Ulrike Ravens-Sieberer (BMC, 2024)
Abstract Background Mental health and health-related quality of life (HRQoL) in children and adolescents deteriorated during the COVID-19 pandemic. The aim of this population-based longitudinal study was to explore whether distinct mental health trajectories in youths can be identified over the course of the pandemic. Methods Mental health problems (MHP), psychosomatic symptoms and HRQoL were assessed at five time points between May 2020 and October 2022 in 744 children and adolescents aged 7 to 20 years using established instruments. We used generalized mixture modeling to identify distinct mental health trajectories and fixed-effects regressions to analyse covariates of the identified profiles of change. Results We found five distinct linear latent trajectory classes each for externalising MHP and psychosomatic symptoms and four trajectory classes for internalising MHP. For HRQoL, a single-class solution that indicates a common development process proved to be optimal. The largest groups remained almost stable at a low internalising and externalising symptom level (64 to 74%) and consistently showed moderate psychosomatic symptoms (79%), while 2 to 18% showed improvements across the pandemic. About 10% of the youths had consistently high internalising problems, while externalising problems deteriorated in 18% of youths. Class membership was significantly associated with initial HRQoL, parental and child burden, personal resources, family climate and social support. Conclusions The mental health of most children and adolescents remained resilient throughout the pandemic. However, a sizeable number of youths had consistently poor or deteriorating mental health. Those children and adolescents need special attention in schools and mental health care.